Physical, psychological and sexual effects in multi-ethnic Malaysian women who have undergone hysterectomy - Wong, L.P.; Arumugam, K. (2012)
Aim: The postoperative effects on Asian women after hysterectomy have not been fully explored. This study was undertaken to investigate the physical, psychological and sexual functioning effects in multi-ethnic Malaysian women who have undergone hysterectomy. Material and Methods: A cross-sectional questionnaire-based study was conducted on women who underwent hysterectomy at the Gynecological Outpatient Clinic, University of Malaya Medical Center between November 2008 and October 2009. Results: Postoperative physical and psychological effects were common. Participants with higher household income had a significantly lower number of physical and psychological problems. Young women were more likely to experience psychological effects. There were significant differences between ethnic groups in physical and psychological symptoms. A multivariate model to determine factors associated with sexual functioning identified the importance of sexual relationship, spouse or partner's attitudes, and ethnic groups as significant covariates. Conclusion: The findings underscore the importance of ethnic-based approaches to counseling to mitigate the psychological effects of hysterectomy and to focus on young women with low socioeconomic status.